HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KEJADIAN HIPERTENSI PADA AKSEPTOR KB DI PMB IIN BATININGSASI, DESA SUKOSARI KABUPATEN LUMAJANG - Susilowati, Susilowati; Maulina, Rifzul; Indriati, Ina (NHM PRESS, 2024)
Hormonal contraception can affect the health of birth control acceptors and one of them affects blood pressure. Family planning acceptors who use hormonal contraceptives can cause hypertension, this is caused by hormonal balance disorders that occur when using hormonal contraceptives. The aim of this study was to determine the relationship between the use of hormonal contraception and the incidence of hypertension in family planning acceptors at PMB Iin Batiningsasi, Sukosari Village, Lumajang District. The type of research used is observational analytics with a cross sectional approach. The research population was all hormonal family planning acceptors (Pills, Injections, Implants) who were active for the period 4 January-3 March 2024 at PMB Iin Batiningsasi, Sukosari Village, Lumajang District with a sample of 51 respondents. Sampling used accidental sampling. Data was collected using questionnaires, blood pressure and stethoscopes. Analysis uses univariate analysis and bivariate analysis using the Chi-Square test. The results of the study showed that the type of hormonal contraception used was mostly injectable contraception at 58.6%, and the majority did not have hypertension at 56.9%. The test results using chi-square obtained a p-value of 0.011 < 0.05. There is a relationship between the use of hormonal contraception and the incidence of hypertension in family planning acceptors in PMB Iin Batiningsasi, Sukosari Village, Lumajang District. It is hoped that family planning program users who are at high risk or who already suffer from hypertension should replace the use of hormonal contraceptives with non-hormonal contraceptive methods.